Characterization of the complete chloroplast genome of Salvia leucantha (Lamiaceae). Issue 12 (2nd December 2021) - Zhou, Yan; Zhang, Hongrui; Ping, Hongming; Ding, Yining; Hu, Saiwen; Bi, Guangyao; Li, Cuicui; Li, Heming; Huang, Yong; Guo, Linxiu; Ma, Xingli; Xia, Zhi
Abstract: Salvia leucantha (Lamiaceae) is an important horticultural plant with great ornamental and economic value. Here, we report the complete chloroplast genome of this species. The chloroplast genome was determined to be 151021 bp and the GC contents was 38.0%. The sequence includes a large single copy (LSC) region of 82, 262 bp, a small single copy (SSC) region of 17, 537 bp, and two separated inverted regions of 25, 611 bp each. It contains 130 unique genes, including 85 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Based on the chloroplast genomes data of 26 species in Salvia, our result indicated that S. leucantha, S. tiliifolia, S. hispanica, and S. splendens formed one clade with Bootstrap = 100%. The four species belong to Salvia subgenus Calosphace, and S. leucantha was closely related to Salvia tiliifolia and Salvia hispanica . This result will facilitate population, genetic diversity and phylogenetic studies of S. leucantha .